1999
DOI: 10.1038/sj.ijo.0800883
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity assessment with accelerometers

Abstract: OBJECTIVE: Evaluation of motion sensors, speci®cally accelerometers, as an objective tool for the assessment of physical activity in large populations, over periods long enough to be representative of normal daily life and with minimal discomfort to the subjects. METHOD: Review of validation studies of accelerometers with indirect calorimetry as a reference method. Accelerometers were commercially available one-axial accelerometers: Caltrac 1 , Computer Science Application (CSA) accelerometer, Mini Motionlogge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
151
2
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(157 citation statements)
references
References 14 publications
0
151
2
4
Order By: Relevance
“…This study has several important features. Firstly, it employed omnidirectional motion sensors, which are better for recording sedentary activity compared with mono-axial sensors (Westerkerp, 1999). Secondly, it sited the accelerometer on the ankle to increase the comfort of 72 h continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has several important features. Firstly, it employed omnidirectional motion sensors, which are better for recording sedentary activity compared with mono-axial sensors (Westerkerp, 1999). Secondly, it sited the accelerometer on the ankle to increase the comfort of 72 h continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties involved in taking such measurements are well established (Avons et al, 1988). Conventional techniques used within the general population include pedometry, accelerometry, heart rate monitoring and activity records obtained through diaries or recall (Westerkerp, 1999;Conway et al, 2002). Although doubly labelled water is now the gold standard for the assessment of energy expenditure, the costs associated with this method restrict its use in population studies (Goldberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Westerterp 13 has suggested that accelerometers are an objective tool for the assessment of PA in large populations over periods long enough to be representative of normal daily life. Since an increase in PA is an effective therapeutic intervention for the prevention and treatment of obesity and its related diseases, a single-axis accelerometer has been developed in Japan for assessing daily PA over long periods (6 weeks).…”
Section: Introductionmentioning
confidence: 99%
“…4 One of the issues identified for physical activity assessment was an inability to quantify trends in physical activity using currently available data. 5 There is increasing interest in objective monitoring of daily physical activity using electronic motion sensors, including accelerometers 6,7 and pedometers. 8 -10 This shift was apparent in the June 2000 Research Quarterly for Exercise and Sport Measurement of Physical Activity Special Issue 11 and again in the September 2000 Medicine and Science in Sports and Exercise Measurement of Moderate Physical Activity: Advances in Assessment Techniques Issue.…”
Section: Introductionmentioning
confidence: 99%